PERKEMBANGAN HUKUM ACARA PERADILAN TATA USAHA NEGARA TERKAIT DENGAN KEWENANGAN MENGADILI DAN PERMASALAHAN HUKUMNYA - Diani Kesuma (Jurnal Hukum dan Bisnis (Selisik), 2020)
The development of the procedure in Administration Court is the consequences from the issuanceLaw No 30 Year 2014 Concerning Government Administration. One of the legal consequence,there is paradigm changes of authority to adjudicate related to the Unlawful Act done by the ruler,in this matter government official which is knows as Onrechtmatige Overheidsdaad (OOD) whichpreviously is the authority of District Court, based on Article 1365 of Indonesian Civil Code, theloses classified as civil law as a result of government action. Further the authorization toadjudicate Unlawful Act by the government become jurisdiction of State Administration Court.Several legal problems are found related to the transition of authority to adjudicate in StateAdministration Court. Supreme Court has issued six (6) Supreme Court Regulations, on theregulation is Supreme Court Regulation No 2, 2019 Concerning Guidelines of dispute resolutionof government action and authority to adjudicate Unlawful Act by government institution and/orofficer Onrechtmatige Overheidsdaad (OOD). Unlawful Act is identical with the claim forcompensation, however there is no regulation as the legal ground related to how much themaximum and minimum limitation could be claimed in the case related Unlawful Act by theGovernment officer and also whether or not there is immaterial claim in the future